International cooperation of states in outer space exploration (International relations and international law Journal, 2020)
State cooperation in space research is one of the priority topics of international space law. Thecalls for international cooperation contained in many documents on space law are aimed at preventingthe transformation of outer space into a conflict zone. Space cooperation is a very effective way of theconfidence-building, because it can reduce mutual suspicion, increase mutual trust and achieve mutualbenefits. The space has become a powerful thruster of scientific and technological progress. This trendis one of many indicators pointing to the global trend involving key actors making a decision to makespace activities a priority. Many countries come to the understanding that international cooperation isthe best means of realization of space programs. At that, the issue of forms of such cooperation gainsspecial importance. It is difficult to think of international space law and the governance of internationalaffairs in isolation from international organizations. The states have joined their efforts in the frameworkof international organizations with the aim of cooperation in the space sector. In this article we will try toanalyze the legal foundations of international cooperation of states in outer space exploration.Key words: international space law, legal regime of the outer space, international responsibility ofstates, space activities of mankind, global role players.